2016
DOI: 10.1111/jonm.12361
|View full text |Cite
|
Sign up to set email alerts
|

Nurse administrators’ intentions and considerations in recruiting inactive nurses

Abstract: Nurse administrators can reduce the nursing shortage by recruiting inactive nurses. Re-entry preparation programmes should be implemented that will provide inactive nurses with knowledge of the current medical environment and the skills required to improve their nursing competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…Unlike workers in the private sector, medical and nursing professionals usually have a career development path due to long-term vacancies in the profession. Although some nurses may not enjoy their career development and pathway, due to the social, cultural, and financial background, human resources in the nursing profession are relatively stable [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike workers in the private sector, medical and nursing professionals usually have a career development path due to long-term vacancies in the profession. Although some nurses may not enjoy their career development and pathway, due to the social, cultural, and financial background, human resources in the nursing profession are relatively stable [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although work–life responsibilities are not balanced due to human resource shortages, it is important to increase the overall enrolment and experience of nursing students and in-service nursing professionals in order to ensure adequate workforce management [ 9 ]. A previous study [ 2 , 10 ] indicated that a large number of mid-level and senior-level nursing professionals decided to leave the profession due to poor administrative management, overloaded working responsibilities, insufficient salaries, and regular overtime. However, many hospital leaders, clinical managers, policymakers, and government leaders do not have solid and tailor-made human resource plans for this particular workforce (i.e., nursing professionals), as general human resources planning may not be able to respond to the needs of the medical and nursing areas [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides ineffective human resources management, recruitment in the medical and nursing profession is not the same as in other nonprofit and profit-making industries. Based on the current nonprofit management scheme, many human resources professionals advocate that the medical and nursing profession may share significant elements and factors with education, social care, and psychology professions [ 10 , 12 ]. Although these fields are generally considered to be nonprofit, medical and nursing professionals may start their own business-oriented clinics and hospitals for profit-making purposes.…”
Section: Introductionmentioning
confidence: 99%
“…From our analysis, considering fit when recruiting for NFP could help identify nurses that understand public health, home-visitation, and working with families living in complex situations of disadvantage. Recruitment research in healthcare primarily focuses on broad strategies to encourage practitioners into the field to address shortages [ 11 , 26 , 59 – 61 ]. Less is known about recruiting for fit within nursing.…”
Section: Discussionmentioning
confidence: 99%